Big think videos on sociology - Smolan, Rick.; Safari eBooks ([Place of publication not identified] : FT Press, 2015)
"A Selection of Expert Video Content from Big Think on hot topics in sociology, including gender discrimination, big data, Millennials, and the science of falling in love."--Resource description page.
Title from resource description page (viewed June 18, 2015)
Presenter, Rick Smolan ... [and nine others].
Keywords: Sociology; Electronic books